Learning to provide family care to Alzheimer patients: bibliography - María Elena Ferrer Hernández; Luis Cibanal Juan (Universidad de Alicante, 2012)
Revising the published bibliography in the ten latest years on learning how to provide family care to Alzheimer patients is the purpose of this article. A systematic and full revision of literature published at national and international level within the main data bases - Spanish as well as foreign - PubMed, Cuiden, CINAHL, PshycInfo, EMBASE, Cochrane and IME (CESIC) was done. Later on some other publications which fulfilled the criteria for being included were selected. A manual searching to identify those articles published in Spanish journals, either indexed or non indexed, not found by electronic means, was also considered. Criteria for including certain articles in the searching were as follows: scientific articles, originals, published from January 2007 up to October 2007, written in English, Spanish, Portuguese or French, those focused directly or indirectly in the prediction, description of variables related to learning and educating the family care taker of Alzheimer patients. All bibliography references in connection with the so called topic were taken into consideration. According to the literature revised it was found most of the care takers did not receive a previous education or followed a proper learning course on how to deal with an Alzheimer patient. They learn by themselves in the day-to-day practice, as self-taught, simply performing, doing wrong or doing right. In that learning process care takers receive some sort of help and advice from the own experience of those other family members who have been through a similar situation. It would be necessary to further deepen in qualitative searching methodology within the care taker experiences and in their day-to-day context, close to their difficulties and achievements. The advisable investigation in this area could also be of paramount importance to design new services which will contribute to complement the existing ones, and would be indeed an appropriate way to develop the take carers learning.